An Integrative Learning Model to Improve Problem-Solving and Creative Thinking Abilities, Collaboration, and Motivation - Wawan, Wawan; Retnawati, Heri; Setyaningrum, Wahyu (Islamic Guidance and Counseling Journal, 2023)
Various empirical reseach show that the ability to problem-solving, creative thinking, collaboration, and motivation to learn mathematics in Indonesia is relatively low. This research aims to develop a project-based mathematics learning model integrated with ethnomathematics and technology. Furthermore, this research also aims to determine the feasibility, practicality, and effectiveness of the developed model in improving problem-solving skills, creative thinking, collaboration, and motivation to learn mathematics. This research approach is Research and Development (RnD), which refers to the Borg and Gall model. The level of validity of models, learning tools, and assessment instruments is proven through the Aiken validity index. The model's practicality was analyzed based on the results of observations of product implementation and student responses. Meanwhile, the model's effectiveness was analyzed using the t-test, One-Way MANOVA, and n-gain. Based on the results of proving the model's validity, the Aiken validity index is .88, and the estimated reliability coefficient is .76, indicating that the developed model meets the valid and reliable criteria. Furthermore, based on the results of the observational analysis of the implementation of the model at the main field-testing stage, the practicality rate of the model was 88% (very practical), and the rate of student responses was 73% (practical). Multivariate and univariate test results show that project-based learning models integrated with ethnomathematics and technology effectively improve problem-solving skills, creative thinking, collaboration, and learning motivation. The project type and the variables measured number are the this research novelty. These research findings can be reference material and alternative solutions for teachers in designing a new learning culture and improving the learning quality.